Theory of mind in utterance interpretation: the case from clinical pragmatics - Cummings, Louise (Frontiers in Psychology, 2015)
The cognitive basis of utterance interpretation is an area that continues to provoke intense theoretical debate among pragmatists. That utterance interpretation involves some type of mind-reading or theory of mind (ToM) is indisputable. However, theorists are divided on the exact nature of this ToM-based mechanism. In this paper, it is argued that the only type of ToM-based mechanism that can adequately represent the cognitive basis of utterance interpretation is one which reflects the rational, intentional, holistic character of interpretation. Such a ToM-based mechanism is supported on conceptual and empirical grounds. Empirical support for this view derives from the study of children and adults with pragmatic disorders. Specifically, three types of clinical case are considered. In the first case, evidence is advanced which indicates that individuals with pragmatic disorders exhibit deficits in reasoning and the use of inferences. These deficits compromise the ability of children and adults with pragmatic disorders to comply with the rational dimension of utterance interpretation. In the second case, evidence is presented which suggests that subjects with pragmatic disorders struggle with the intentional dimension of utterance interpretation. This dimension extends beyond the recognition of communicative intentions to include the attribution of a range of cognitive and affective mental states that play a role in utterance interpretation. In the third case, evidence is presented that children and adults with pragmatic disorders struggle with the holistic character of utterance interpretation. This serves to distort the contexts in which utterances are processed for their implicated meanings. The paper concludes with some thoughts about the role of theorizing in relation to utterance interpretation.